Innovative Research Methods: Using Simulation to Evaluate Health Care Policy - Green, Ellen P; Dong, Yue; Shah, Nilay D (Simulation in healthcare : journal of the Society for Medical Simulation, 2024)
Health care policies have the potential to improve patient outcomes, access to care, and reduce health disparities. However, new policy is often tested in the field, where unintended consequences are paid for by patients. In this perspective, we argue that health care simulations, which can elucidate the potential for policy to hinder clinicians' ability to provide high-quality care, are a complement to large-scale policy evaluations in the field.